High‐Performance Field Effect Transistors Using Electronic Inks of 2D Molybdenum Oxide Nanoflakes. (20th November 2015) - Alsaif, Manal M. Y. A.; Chrimes, Adam F.; Daeneke, Torben; Balendhran, Sivacarendran; Bellisario, Darin O.; Son, Youngwoo; Field, Matthew R.; Zhang, Wei; Nili, Hussein; Nguyen, Emily P.; Latham, Kay; van Embden, Joel; et al.
Abstract : Planar 2D materials are possibly the ideal channel candidates for future field effect transistors (FETs), due to their unique electronic properties. However, the performance of FETs based on 2D materials is yet to exceed those of conventional silicon based devices. Here, a 2D channel thin film made from liquid phase exfoliated molybdenum oxide nanoflake inks with highly controllable substoichiometric levels is presented. The ability to induce oxygen vacancies by solar light irradiation in an aqueous environment allows the tuning of electronic properties in 2D substoichiometric molybdenum oxides (MoO3− x ). The highest mobility is found to be ≈600 cm 2 V −1 s −1 with an estimated free electron concentration of ≈1.6 × 10 21 cm −3 and an optimal I On / I Off ratio of >10 5 for the FETs made of 2D flakes irradiated for 30 min ( x = 0.042). These values are significant and represent a real opportunity to realize the next generation of tunable electronic devices using electronic inks. Abstract : Electronic inks of 2D MoO3 − x flakes based on a solar light irradiation in liquid‐phase exfoliated method are used for developing channels FETs for future high‐performance printed nanoelectronic devices. It is shown that the carrier concentration, energy band, and carrier charge mobility in 2D MoO3− x ‐based FETs can be tuned and the optimal substoichiometric value with the maximum transconductance is obtained.